PENGARUH PENDEKATAN VAK (VISUALIZATION, AUDITORY, KINESTETIC) TERHADAP HASIL BELAJAR FISIKA SISWA SMPN 10 MATARAM - Siswadi Siswadi; Susilawati Susilawati; Hikmawati Hikmawati (Postgraduate, University of Mataram, 2018)
This research aimed to examine the effect of VAK approach (Visualization, Auditory, Kinestetic) towards the result of learning physics of students at SMPN 10 Mataram. The kind of research used was experimental design with design of research was randomized posttest only control design. The sampling technique used was cluster random sampling. Population in this research was all the students from the eight grade at SMPN 10 Mataram, while the sample was 25 students of class VIII A as the experimental group and 27 students of class VIII B as the control group. The data obtained was analyzed by using t-test of two-tailed. t-count was 4.78 and t-table was 2.00 with significance level 0.05. Hence, t-table is smaller than t-count or t-count is bigger than t-table. It means that Null Hypothesis was rejected and Alternate Hypothesis was accepted. It means that the application of VAK Approach (Visualization, Auditory, Kinestetic) affects the results of learning physics of students.Keywords: VAK Approach